Effect of Marble Dust and Furnace Slag as Sand Replacement Materials on Strength Properties of Pavement Quality Concrete (PQC) - Thakur, Yogesh Kumar (My University, 2014)
The demand for utilization of industrial by-products and wastes in road pavements is increasing and becoming more important. Government policies and public awareness is also contributing to the enhancement of both this demand and utilization. Various slags such as blast furnace and steel slag have been widely used in road pavements. On the other hand, marble dust creates large scale environmental pollution. Therefore, it could be possible to prevent the environmental pollution and to consume fewer natural resources as well through its utilization in increasing demand for road construction. The present study aims at, developing pavement quality concrete mixtures incorporating marble dust and furnace slag as a partial fine aggregate replacement material. In this study the effect of marble dust & furnace slag on strength properties of Pavement Quality Concrete (PQC) are reported and the effect on the slab thickness of PQC pavement for the achieved flexural strength of the concrete mixtures incorporating marble dust and furnace slag has also been studied. The study shows that the marble dust can be effectively replace sand up to 15% and furnace slag can be used up to 20% as replacement of sand in PQC. The maximum flexural strength is achieved for the mix containing 10% marble dust and 10% furnace slag as partial replacements of sand. The flexural strength increase is significant for mixes containing marble dust and furnace slag, with a combination up to certain limits of 25 to 30% in development of pavement quality concrete. This not only fulfills the IRC specification of PQC but also saves the other material ingredients used in concrete leading to economic design of the concrete slab for the pavement.
ME, CED
Keywords: PQC; Marble Dust; Furnace Slag; IRC 58